Satellite data in monsoon researchSatellite data in monsoon research - Mausam, Editor; DESAI, PRANAV S. (MAUSAM, 1990)
The Space Applications Centre of the Indian Space Research Organization is engaged in exploring and demonstrating the application of satellite observation in various disciplines. In this review paper the utilization of satellite data in monsoon research, in progress at SAC and ISRO Headquarters is described: Most of the studies use satellite data in combination with insitu data.